1997
DOI: 10.1093/emboj/16.4.695
|View full text |Cite
|
Sign up to set email alerts
|

The membrane-proximal intracytoplasmic tyrosine residue of HIV-1 envelope glycoprotein is critical for basolateral targeting of viral budding in MDCK cells

Abstract: Budding of retroviruses from polarized epithelial Madin–Darby canine kidney cells (MDCK) takes place specifically at the basolateral membrane surface. This sorting event is suspected to require a specific signal harbored by the viral envelope glycoprotein and it was previously shown that, as for most basolateral proteins, the intracytoplasmic domain plays a crucial role in this targeting phenomenon. It is well known that tyrosine‐based motifs are a central element in basolateral targeting signals. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
176
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(190 citation statements)
references
References 80 publications
(138 reference statements)
13
176
1
Order By: Relevance
“…Interaction with AP1 would be expected to occur in the trans Golgi network and may direct newly synthesised Env to endosomes. Whether this is required to divert newly synthesised Env to lysosomes (28), thereby providing an additional mechanism to limit Env expression on the cell surface, or plays a more significant role in polarised sorting or recycling of Env remains to be determined (3,33). By contrast to studies in which the HIV-1 Env endocytosis signal was shown to interact with three different m subunits (17), we failed to detect any interaction between a peptide encoding the entire BK28 cytoplasmic domain and AP3 using an optical biosensor.…”
mentioning
confidence: 99%
“…Interaction with AP1 would be expected to occur in the trans Golgi network and may direct newly synthesised Env to endosomes. Whether this is required to divert newly synthesised Env to lysosomes (28), thereby providing an additional mechanism to limit Env expression on the cell surface, or plays a more significant role in polarised sorting or recycling of Env remains to be determined (3,33). By contrast to studies in which the HIV-1 Env endocytosis signal was shown to interact with three different m subunits (17), we failed to detect any interaction between a peptide encoding the entire BK28 cytoplasmic domain and AP3 using an optical biosensor.…”
mentioning
confidence: 99%
“…The Env-negative proviral construct harboring a mutation in the matrix protein HXBH10Env-(KpnIfs)⌬16-18 was generated by cloning the SalI-BamHI (HXBH10 nucleotide positions 5372 and 8058, respectively; +1 = site of initiation of transcription) fragment of HXBH10Env-(KpnIfs) into HXBH10⌬16-18; both plasmids have been described elsewhere. 25,37,38 Cell lines and antisera The 293T, COS, HeLa, HeLaCD4 39 and HeLaCD4LTR␤-gal 33 cells were maintained in DMEM supplemented with 5% fetal calf serum (FCS) and 1% streptomycin and penicillin. Human antiserum No.…”
Section: Methodsmentioning
confidence: 99%
“…162 against HIV proteins has been described elsewhere. 37 The goat antiserum against MuLV Gag (76S000127 and 79S000804) was obtained from Quality Biotech (Biological Carcinogenesis Branch, NCI, Camden, NJ, USA); antiserum raised against MuLV Env (80S00019) was also obtained from Quality Biotech.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations